ANALISIS ASESMEN TES TERTULIS KETERAMPILAN MENGEVALUASI DAN MERANCANG PENYELIDIKAN ILMIAH YANG DIGUNAKAN PADA MATAPELAJARAN IPA-BIOLOGI SMP - Melinda Yustiva Sumarra, - (2020)
This study aims to analyze the written tests on the skills of evaluating and designing scientific investigations on Biology subject in Junior High Schools. The subjects of this study are six public and private secondary schools (SMP) based on the National Examination (UN) scores. To uncover the use of the evaluating and designing scientific investigations test, descriptive statistical research methods and qualitative analysis are used. The Mid Term Semester Test (PTS) and The Final Semester Assessment (PAS) sets on Natural Science subject especially Biology are used to analyze the skills of evaluating and designing the scientific investigations. This research produced a blueprint test and parallel questions from the results of the development of the PISA framework which is integrated with the 2013 curriculum. According to the PISA framework, a parallel problem is developed based on the context of the investigation of Biology in ecosystems (environment), science laboratories, and health in natural science subjects in Biology of Junior High Schools. The results showed that the percentage of PTS and PAS questions based on the skills of evaluating and designing scientific investigations is 1.87% (a small portion). The main test in the school is still focused on memorization or memorizing, basic understanding, not based on scientific investigation. This research had produced a blueprint test recommendation and three parallel test sets to measure the skills of evaluating and designing scientific investigations. Characteristics of the recommended questions are based on the data, scientific investigations and real-life contexts.